Experimental investigation on fibre-reinforced lightweight aggregate concrete beams at elevated temperature - Goh, Jamie Po Yan (Nanyang Technological University, 2023)
This research delves into the critical issue of structural integrity during fire incidents and explores the application of lightweight aggregate concrete (LWAC) in the construction sector. Exposure to fire can result in structural components weakening, potentially leading to deformation and failures with grave consequences for both structures and human safety. To emphasize the gravity of the matter, we reference data from the Singapore Civil Defence Force, highlighting the frequent occurrence of fire-related incidents in a compact nation like Singapore.